Análisis del sistema unitario de compensación regional de pagos en la exportación de atún en conserva hacia Venezuela - Vera Cortez, Marco Antonio (2018)
The present titling work whose subject corresponded to the analysis of the unitary system of regional compensation of payments in the export of canned tuna to Venezuela, has had a descriptive methodological approach, and used levels of explanatory, deductive and inductive research, as far as to carry out the respective analysis proposed by the general objective, which was directed towards the conclusion of the analysis of the development of Ecuadorian canned tuna exports to the Venezuelan market, in order to determine the strengths and weaknesses presented by the Unitary System of Regional Compensation of Payments (SUCRE). For the data collection, 6 structured and pre-designed interviews were carried out, thanks to the Skype program, the managers and representatives of tuna exporters in Ecuador, as well as a representative of the central bank, who had notion and information on the subject addressed; finally the work was concluded in the realization of the proposal, being able to carry out and carry out the analysis to the Sucre system applying a SWOT matrix to the development of the system in the export of canned tuna from the Ecuadorian market to the market in Venezuela, thus giving objectives………..